Performance of a loop-mediated isothermal amplification assay (Isoplex CRE-ART) to detect common carbapenemase-encoding genes in Gram-negative bacteria. Issue 7 (12th July 2021) - Berneking, Laura; Asar, Lucia; Both, Anna; Berinson, Benjamin; Aepfelbacher, Martin; Lütgehetmann, Marc; Rohde, Holger
Abstract : Carbapenem-resistant Gram-negative bacteria (CR-GNB) are a major source of nosocomial infections worldwide. In this study, the ability of a loop-mediated isothermal amplification (LAMP)-based method (Isoplex CRE-ART) to rapidly detect carbapenemase-encoding genes bla OXA-48-like, bla OXA-23-like, bla OXA-24-like, bla KPC, bla VIM, bla NDM and bla IMP in 231 carbapenem-resistant Enterobacterales, Pseudomonas aeruginosa and Acinetobacter baumannii isolates was investigated. The accuracy of the LAMP test was compared to results of molecular isolate characterization using a Laboratory Developed Test multiplex carbapenemase PCR assay. The LAMP test correctly identified the presence of on-panel carbapenemases with a sensitivity of 99.16 % [95 % confidence interval (CI): 95.39–99.96 %] and a specificity of 98.21 % (95 % CI: 93.72–99.68 %) in 60 min. Our findings suggest that the Isoplex CRE-ART assay is able to rapidly identify carbapenemase genes in CR-GNB and improves options for pathogen characterization in the context of clinical microbiological and infection control diagnostics.